Thermo-magnetic characterization of Mn55Al45C2 for high temperature devices - Mahmoud A. Hamad; Tahani R. Aldhafeeri; Hatem R. Alamri; Mohamed E. Harb (Physics Open)
The magnetocaloric effectin Mn55Al45C2 alloys synthesized via induction heating is investigated, ranging from 450 to 650 K. The experimental and modelled thermo-magnetization for Mn55Al45C2 alloys at 0.1 T agree well, highlighting that PM is a reliable method for simulating thermo-magnetization for Mn55Al45C2 alloys. The maximum values magnetic entropy changes for Mn55Al45C2 alloys are 55 mJ/kg.K and 47 mJ/kg.K, respectively, with full-width at half-maximum of 70 and 65 K. The relative cooling power and refrigerant capacity values reaches 3.88 J/kg and 2.8 J/kg, respectively. It is proposed that Mn55Al45C2 be used as attracting magnets in magnetic refrigeration to address the issue of rising battery and motor temperatures, hence improving the electric and hybrid vehicles' performance.